A Review of Proton Conductivity in Cellulosic Materials - Selyanchyn, Olena; Selyanchyn, Roman; Lyth, Stephen M. (Frontiers in Energy Research, 2020)
Cellulose is derived from biomass and is useful in a wide range of applications across society, most notably in paper and cardboard. Nanocellulose is a relatively newly discovered variant of cellulose with much smaller fibril size, leading to unique properties such as high mechanical strength. Meanwhile, electrochemical energy conversion in fuel cells will be a key technology in the development of the hydrogen economy, but new lower cost proton exchange membrane (PEM) materials are needed. Nanocellulose has emerged as a potential candidate for this important application. In this review we summarize scientific developments in the area of cellulosic materials with special emphasis on the proton conductivity, which is the most important parameter for application in PEMs. We cover conventional cellulose and nanostructured cellulose materials, polymer composites or blends, and chemically modified cellulose. These developments are critically reviewed, and we identify interesting trends in the literature data. Finally, we speculate on future directions for this field.